Character Education And Social Behavior: The Mediating Function Of Emotional Development - Emilda Oktavia; Ike Kusdyah (International Journal of Management, Innovation, and Education, 2025)
This study examines the relationship between character education and children’s social behavior by investigating the mediating role of emotional development in early childhood education settings. A quantitative survey design was employed involving 60 teachers from Palm Kids Preschool in Palembang, Indonesia. Data were collected using structured questionnaires developed from indicators of character education, emotional development, and social behavior. The data were analyzed through simple linear regression and mediation analysis using the Sobel test. The findings reveal that character education has a positive and significant effect on both emotional development and children’s social behavior. Emotional development was also found to significantly influence social behavior. Furthermore, the mediation analysis confirmed that emotional development significantly mediates the relationship between character education and social behavior. These results indicate that character education contributes not only directly to the enhancement of children’s social behavior but also indirectly through strengthening emotional competencies. The study highlights the importance of integrating character-building practices with emotional development strategies in early childhood education to foster adaptive and prosocial behavior. This research contributes to the growing discourse on socio-emotional learning and character-based education by providing empirical evidence from the context of early childhood education in Indonesia.